PENGARUH RENDAM KAKI AIR HANGAT TERHADAP PENURUNAN TEKANAN DARAH PADA PENDERITA HIPERTENSI DI PSTW GAU MABAJI KABUPATEN GOWA - Zaenal Zaenal (Stikes Graha Edukasi Makassar, 2018)
Purpose of the study: The aim of this study was to effect the warm water foot soak to decrease blood pressure in elderly at PSTW Gau Mabaji Gowa Regency. Methods: The design of this study was pre-experimental with the type of one-group t-test design in which the objective was to determine the effect of warm water foot baths on the decrease of hypertension in elderly in PSTW Gau Mabaji Gowa District. The sample size in this study are 10 respondents who match the inclusion criteria. Data collection is done by observation. In this research use paired sample t-test. at significance level ? = 0.05. Results: The results of the study showed that there was a warm water foot effect on blood pressure drop in elderly people at PSTW Gau Mabaji Gowa District (p = 0.000). Discussion: Blood pressure is 120-140 mmHg systolic pressure and 80-90 mmHg diastolic pressure. Seseornag expressed hypertension when blood pressure> 140/90 mmHg. Conclusion: there is influence of warm water foot soak to decrease of hypertension in elderly in PSTW Gau Mabaji Gowa Regency. Suggestion: The results of this research can be used as input for all parties, especially nurses who work in PSTW Gau Mabaji Gowa Regency in applying the implementation of warm water foot therapy in patients with hypertensive disorders